2017
DOI: 10.1016/j.mimet.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A real-time PCR assay for accurate quantification of the individual members of the Altered Schaedler Flora microbiota in gnotobiotic mice

Abstract: Changes in the gastrointestinal microbial community are frequently associated with chronic diseases such as Inflammatory Bowel Diseases. However, understanding the relationship of any individual taxon within the community to host physiology is made complex due to the diversity and individuality of the gut microbiota. Defined microbial communities such as the Altered Schaedler Flora (ASF) help alleviate the challenges of a diverse microbiota by allowing one to interrogate the relationship between individual bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 43 publications
(78 reference statements)
1
62
0
Order By: Relevance
“…ASF mice are a reliable model to study how the addition of a specific bacterial strain to a stable community influences immunological and metabolic pathways or affects disease outcomes (Gomez de Aguero et al, 2016; Shen et al, 2015)(Gomes-Neto et al, 2017). Having observed that fluconazole-induced fungal dysbiosis exerts persistent impacts on systemic immunity and AAD in mycobiota-sufficient specific pathogen-free (SPF) mice, without directly targeting either commensal bacteria or the host, we asked whether a supplementation with intestinal fungi can recapitulate the disease phenotype in MyF-ASF mice.…”
Section: Resultsmentioning
confidence: 99%
“…ASF mice are a reliable model to study how the addition of a specific bacterial strain to a stable community influences immunological and metabolic pathways or affects disease outcomes (Gomez de Aguero et al, 2016; Shen et al, 2015)(Gomes-Neto et al, 2017). Having observed that fluconazole-induced fungal dysbiosis exerts persistent impacts on systemic immunity and AAD in mycobiota-sufficient specific pathogen-free (SPF) mice, without directly targeting either commensal bacteria or the host, we asked whether a supplementation with intestinal fungi can recapitulate the disease phenotype in MyF-ASF mice.…”
Section: Resultsmentioning
confidence: 99%
“…Male and female C3H/HeN mice (8-10 weeks old) harboring the Altered Schaedler Flora (ASF) microbiota from birth were bred and maintained under gnotobiotic conditions at the University of Nebraska-Lincoln Gnotobiotic Mouse Facility as previously described. 47,48 Members of ASF community include: ASF 356, Clostridium sp. ; ASF 360, Lactobacillus intestinalis; ASF361, Lactobacillus murinus; ASF 457, Mucispirillum schaedleri; ASF 492, Eubacterium plexicaudatum; ASF 500, Pseudoflavonifractor sp.…”
Section: Micementioning
confidence: 99%
“…49,50 Prior to inoculation with E. coli, ASF-bearing mice were transferred from flexible film isolators to a positive pressure, individually-ventilated caging system and maintained as previously reported. 48 Each mouse received 1 x 10 8 E. coli CFU in 200 µL of LB broth via oral gavage. Successful E. coli colonization was verified by collecting fecal samples 10 days post-inoculation and plating on Eosin Methylene Blue (EMB) agar plates (Difco).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…In order to generate mice that harbor the Altered Schaedler Flora (ASF) microbiota, germ-free (GF) mice were gavaged with cecal contents of ASF mice. Colonization was determined by qPCR as previously reported (26). Sulfur amino acids (Saa) diets were formulated based on previous literature (27,28) to represent edge cases of Saa consumption,…”
mentioning
confidence: 99%